The ante-tempus novel: prevention and patienthood in recent speculative fiction. Issue 6 (3rd July 2019) - Liorsi, Benedetta
ABSTRACT: This article introduces a new medical subjectivity generated by the drive towards prevention that increasingly organises the discourses and practices of medicine, as well as war, state security and economy. The ante-tempus patient is the subjectivity emerging at a moment in time in which medical advances and interventions are shaping the present according to future needs, in order to face anticipated threats to human health. Contemporary science fiction offers a fertile ground for investigating this, as well as the resulting anxieties about mass-medicalisation. The first part of the article explores the concept of preventative mass-medicalisation and the exploitation and harvesting of 'health' in neoliberal societies. In the second part, the speculative novel The Unit [Ninni Holmqvist, trans. Marlaine Delargy (Oxford: Oneworld Publications, [2006] 2010)] exemplifies and contextualises the key features of ante-tempus patienthood. This medical subjectivity embodied by the novel's main characters represents the outcome of the attempt to create a medical utopia. In this society of medical management, biological exploitation, forced medicalisation and self-sacrifice merge with neoliberal ideology, casting the discourse of preventative medicine in dystopian terms.